Down syndrome and microRNAs - Brás, Aldina (2022)
In recent years numerous studies have indicated the importance of microRNAs (miRNA/miRs) in human pathology. Down syndrome (DS) is the most prevalent survivable chromosomal disorder and is attributed to trisomy 21 and the subsequent alteration of the dosage of genes located on this chromosome. A number of miRNAs are overexpressed in down syndrome, including miR-155, miR-802, miR- 125b-2, let-7c and miR-99a. This overexpression may contribute to the neuropathology, congenital heart defects, leukemia and low rate of solid tumor development observed in patients with DS. MiRNAs located on other chromosomes and with associated target genes on or off chromosome 21 may also be involved in the DS phenotype. In the present review, an overview of miRNAs and the haploinsufficiency and protein translation of specific miRNA targets in DS are discussed. This aimed to aid understanding of the pathogenesis of DS, and may contribute to the development of novel strategies for the prevention and treatment of the pathologies of DS.